Improving PAI Learning Outcomes Through Audio Visual Media Class IV at SDN 06 Padang Sawah - Erdanis (BiCED Proceeding, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education (PAI) in grade IV at SDN 06 Padang Sawah through the application of audio-visual media and differentiated learning models. The research was conducted in two cycles, each including planning, implementation, observation, and reflection activities. In Cycle I, the use of audio-visual media was not fully effective in improving student learning outcomes, with 11 students not meeting the Minimum Completion Criteria (KKM). Based on the reflection of Cycle I, in Cycle II, the researcher enhanced the quality of audio-visual media use and involved students in group discussions to deepen the material through a differentiated approach. As a result, in Cycle II, 15 students (83.3%) achieved KKM, while 3 students (16.7%) did not meet the criteria. This study shows that the application of audio-visual media and differentiated learning models can improve students' learning outcomes in PAI education.